Clinical and Epidemiological Findings of Pediatric Onset Multiple Sclerosis in East-Azerbaijan, Iran; A Population-based Study - Nasiri, Ehsan; Naseri, Amirreza; Talebi, Mahnaz (Iranian Journal of Child Neurology, 2023)
Objectives Multiple sclerosis (MS) is among the most prevalent chronic immunemediated inflammatory diseases. If MS onset is under 18, it is defined as pediatric-onset MS (POMS). This study aimed to determine the clinical and epidemiological aspects of POMS. Materials & Methods This population-based study was conducted in East-Azerbaijan (EA) province and concerned POMS patients. The data concerning almost all of the POMS patients of the province was gathered from the only MS registry center in the university hospital of the Tabriz University of Medical Sciences by the end of 2017. The diagnosis of patients was based on McDonald’s criteria. Results Out of 2976 total cases of MS, eighty-five (2.85%) were POMS. The overall regional prevalence of POMS was 11.67 per 100,000 (95% CI:9.43-11.43). Sixty-seven cases were female (prevalence: 18.94 per 100,000 [95% CI:14.91-24.07], and eighteen were male (prevalence: 4.80 per 100,000 [95% CI:3.03-7.62]. The crude regional incidence in 2017 was 1.37/100,000 (95% CI:0.74-2.55). The mean age of onset was 15.81±1.33 years, with a minimum age of 12. 71.76% of the patients were diagnosed in the 16- or 17-years old age group. 7.05% had a positive family history, and 87.5% of the patients diagnosed the disease promptly. The most common first clinical presentations were blurred vision (43.75%), sensory (28.12%), cerebellar (15.62%), and brainstem (9.37%) symptoms. Conclusion POMS is not a rare condition, and it mainly affects females. POMS prevalence increases significantly after age 15 years old, and the first manifestation of the disease is usually blurred vision.